Ecological Awareness In The Ogoh-Ogoh Tradition In The Hindu Bali Community Of Sidowaluyo Village, South Lampung - Rio Setiawan .; Luthfi Salim; Muslimin; Shonhaji (UNIB Press, 2025)
The ogoh-ogoh tradition is a cultural practice of the Balinese Hindu community that not only functions as a religious ritual, but also has a relationship with social and environmental dynamics. This study aims to analyze the ogoh-ogoh tradition in relation to the ecological awareness of the Balinese Hindu community in Sidowaluyo Village through the perspective of Julian H. Steward's cultural ecology. The research method used is qualitative with a descriptive-analytical approach through observation, interviews, and documentation studies. The results of the study indicate a transformation in the ogoh-ogoh practice, especially in the use of more environmentally friendly materials and the development of ecological behavior in the community, such as waste management offerings, mutual cooperation in environmental cleanliness, and tree planting activities. The discussion shows that these practices are in line with the values ​​of Tri Hita Karana, especially the palemahan aspect, which emphasizes the harmony of human relations with nature. Thus, the ogoh-ogoh tradition can be understood as a form of cultural adaptation that plays a role in the internalization of ecological awareness in the community.